2022
DOI: 10.1111/iej.13698
|View full text |Cite
|
Sign up to set email alerts
|

Present status and future directions: Canal shaping

Abstract: This narrative review will focus on the evolution, present and future of engine-driven root canal preparation. Root canal preparation changed drastically when Walia in 1988 introduced the use of nickel-titanium (NiTi) alloys in Endodontics. In 2013, five generations of NiTi endodontic instruments had been established based on their metallurgical, mechanical properties and design features. Since then, manufacturers have been introducing further major changes in instrument design and characteristics that have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 135 publications
(159 reference statements)
0
42
0
2
Order By: Relevance
“…The application of NiTi in dentistry and specifically endodontics has been reviewed before, detailing metallurgical properties of the alloy, its’ structure, martensitic transformation ability and its evolutionary design [ 11 , 12 , [23] , [24] , [25] ]. NiTi alloys used in endodontic instruments contain approximately 56% (wt.)…”
Section: Metallurgy Of Nickel–titanium Alloymentioning
confidence: 99%
“…The application of NiTi in dentistry and specifically endodontics has been reviewed before, detailing metallurgical properties of the alloy, its’ structure, martensitic transformation ability and its evolutionary design [ 11 , 12 , [23] , [24] , [25] ]. NiTi alloys used in endodontic instruments contain approximately 56% (wt.)…”
Section: Metallurgy Of Nickel–titanium Alloymentioning
confidence: 99%
“…Furthermore, it has been reported that reciprocating single file systems are more likely to induce dentinal microcracks than continuous rotation file system (Bürklein et al, 2013). However, the results of ex vivo studies, as discussed previously, have been questioned, due to the presence of pre‐existing cracks in the sample selection (Arias & Peters, 2022; De‐Deus et al, 2014). The results of cadaver studies do not show any causal relationship between root canal shaping and the development of dentinal microcracks (Arias et al, 2014; Bahrami et al, 2017), and these results should be considered as more relevant due to absence of pre‐existing cracks (Versiani et al, 2021).…”
Section: Contributory Risk Factorsmentioning
confidence: 99%
“…The technology behind the metallurgy of nickel–titanium (NiTi) alloys allowed for the development of new rotary endodontic files with a variety of designs and improved efficiency and safety [ 1 ], aiming to reduce iatrogenic mishaps, such as deviation or perforation [ 2 ]. Currently, shaping procedures using NiTi rotary instruments are more predictable and easier when compared to manual preparation with stainless-steel files [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The technology behind the metallurgy of nickel–titanium (NiTi) alloys allowed for the development of new rotary endodontic files with a variety of designs and improved efficiency and safety [ 1 ], aiming to reduce iatrogenic mishaps, such as deviation or perforation [ 2 ]. Currently, shaping procedures using NiTi rotary instruments are more predictable and easier when compared to manual preparation with stainless-steel files [ 1 , 2 ]. The NiTi alloys used to produce endodontic instruments have an almost equiatomic ratio of nickel and titanium elements [ 3 , 4 ] and may have three microstructural phases, namely austenite, R-phase, and martensite, responsible for their mechanical behavior [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%